Phytochemical profile of onion (Allium cepa) var. aggregatum: Comparative study of TNAU varieties with a local indigenous - GEETHANJALI, S; KRISHNAN, VEDA; MAHESHWARI, T UMA; ARAVINDARAJAN, S T M (The Indian Journal of Agricultural Sciences, 2024)
Aggregatum onion (Allium cepa L. var. aggregatum Don.) is widely grown and consumed in southern India. Present study was carried during 2020–23 at Anbil Dharmalingam Agricultural College and Research Institute (Tamil Nadu Agricultural University), Tiruchirappalli, Tamil Nadu to map the metabolites and other dietary nutrients contributing to nutraceutical potentials between indigenous varieties and aggregatum onions varieties of Tamil Nadu. Experiment consisted of Co (On) 5 and Co (On) 6 (Tamil Nadu Agricultural University released varieties) and an indigenous variety from Perambalur (PL), Tamil Nadu. In the present study, metabolites of all the 3 varieties were mapped with the GCMS/MS, and the PL was shown to have high phytonutrients with health benefits. Further, in UHPLC, quercetin was identified with a sharp, well resolved symmetrical peak for all the three onion varieties with the retention time of 64.5, 65.5 and 64.5 min respectively. The Co (On) 6 is the improved variety of Co (On) 5 with a quercetin content of 75.05 ± 0.30 mg/kg, followed by PL (11.11 ± 0.51 mg/kg). However, the native cultivar PL (4.52 ± 0.15 mg/kg) has the highest anthocyanin content followed by Co (On) 6 (4.00 ± 0.10 mg/kg). This study therefore, provides preliminary information on metabolites and phenolics in the selected onion varieties of Tamil Nadu.